Knowledge management in evaluating technology: Study on how firm select their technology needs - Mohd Nawi, Mohd Nasrun; Ibrahim, Amlus; Mat, Ab Wahab; Mohd Ariffin, Mazrifirdaus; Asree, Susita (2006)
This paper study the approach of the Knowledge Management concept in making assessment of the technology investment evaluation and benefits identification.It is thus with the increasing amount of technology investment and substantial evidence of failure, together with claims of gaining competitive advantages Evaluation of technology benefits in most cases concerned mainly with either the classification of types of benefits or the initial assessment and justification procedures for identifying and evaluating potential benefits which technology project may deliver.Technology on it own does not deliver benefits.If benefits are derived from technology through business changes, then it is reasonable to assumes that the implication of these changes be assessed before the technology being utilized in order to quantify the potential the potential benefits.It was found out that the decision to invest resources into technology is taken with the help of actin plan (a strategy)aimed at achieving the technology investment target like efficiency (quality of service) improving business process (modeling) and specification of technology benefit objectives.When the evaluation dictates a change to the system, benefit profiles and programmers are updated; it is the perspectives for the technology selection.